Validity and reliability of a social skills scale among Chilean health sciences students: A cross-sectional study - Emilio Rodriguez Macayo; Ruben Vidal-Espinoza; Rossana Gomez-Campos; Cynthia Lee Andruske; Marco Cossio-Bolaños (PAGEPress Publications, 2022)
Currently, there is a growing need to assess social skills in young university students since the use and application of these scales can provide benefits in different situations, such as work, education, clinical and psychological. The objective of the study was to verify the validity and reliability of a social skills scale (SS) for students from three professional health sciences programs in Chile. This information will provide understanding and development of SS among health care team members and between them and patients. A cross-sectional study was designed with 185 Chilean university students (141 males and 44 females). Students were recruited voluntarily from a private university in Chile. Ages ranged from 18 to 30 years old. Goldstein's SS scale (consisting of six dimensions with a total of 50 questions) was used. It was administered virtually. Validity was verified by means of confirmatory factor analysis and reliability through internal consistency. The factor structure of the model confirmed the 50 questions and six dimensions of the scale. In general, the model reflected satisfactory values. Kaiser-Meyer-Olkin's (KMO) test for the adequacy (suitability) of the sample was 0.834, chi squared X2= 4344.8 (gl= 1425, p< 0.000). The comparative fit index (CFI) was 0.45, goodness of fit index (GFI) was 0.56, the root mean square error of approximation (RMSEA) was 0.091, and the % of variance 54%. The communalities reflected values from 0.31 to 0.76. In addition, Cronbach's Alpha values varied from 0.72 to 0.75. In its totality, the scale demonstrated a reliability of 0.75. The SS scale is valid and reliable. It can be used with students from nursing, kinesiology, and speech therapy programs. The results suggest the use and application of the scale with professionals working in higher education.